Comparison of between-training-sessions recovery strategies for world-class BMX pilots - Marquet, L.-A.; Hausswirth, C.; Hays, A.; Vettoretti, F.; Brisswalter , J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To assess the impact of between-training-sessions recovery strategies (passive [PAS], active [ACT], cold-water immersion [CWI], and ingestion of a recovery drink [NUTR]) on maximal cycling performance, perceptions of delayed-onset muscle soreness (DOMS), and fatigue in world-class BMX riders. Methods: Eleven elite BMX athletes, members of the French national team (top country in the 2011 international ranking, 4 medals at the 2012 World Championships, top European country), participated in the study, which involved standardized training periods. Athletes performed 3 maximal-sprint power tests: the first day of the week before the training session and before and after training on the third day of the week (D3). The recovery strategy was randomly assigned to each participant on day 2 immediately after the last training period of the day. Perceptions of DOMS and general fatigue were recorded on D3. Results: After training on D3, the decrease in maximal-sprint power (Pmax) was significantly greater for PAS than with CWI (P = .02) and NUTR (P = .018). Similar results were found with ACT (vs CWI P = .044, and vs NUTR P = .042). Self-reported DOMS and fatigue were significantly greater after PAS than after other strategies. Conclusions: For elite BMX riders, between training days, nutritional and/or CWI recovery strategies appear to be best for reducing muscle fatigue and increasing the capacity to withstand the training schedule.